2019
DOI: 10.1103/physrevlett.122.117205
|View full text |Cite
|
Sign up to set email alerts
|

Barkhausen Noise from Precessional Domain Wall Motion

Abstract: The jerky dynamics of domain walls driven by applied magnetic fields in disordered ferromagnets -the Barkhausen effect -is a paradigmatic example of crackling noise. We study Barkhausen noise in disordered Pt/Co/Pt thin films due to precessional motion of domain walls using full micromagnetic simulations, allowing for a detailed description of the domain wall internal structure. In this regime the domain walls contain topological defects known as Bloch lines which repeatedly nucleate, propagate and annihilate … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 33 publications
3
10
0
Order By: Relevance
“…1a) for different σ is the timeaverage over the second half of the simulation time. For σ = 0, V (B ext ) exhibits a linear increase with B ext up to a Walker field B W ≈ 2.7 mT (in excellent agreement with both the prediction B W = α 2 µ 0 M s N n ≈ 2.6 mT using N n = ∆ πD ln 2 [22], and micromagnetic simulations [21]), at which point V abruptly drops due to the onset of precession of φ. We note that due to weak numerical noise in our implementation, some BLs are present even for σ = 0, and hence the σ = 0 curve shown in Fig.…”
supporting
confidence: 82%
See 2 more Smart Citations
“…1a) for different σ is the timeaverage over the second half of the simulation time. For σ = 0, V (B ext ) exhibits a linear increase with B ext up to a Walker field B W ≈ 2.7 mT (in excellent agreement with both the prediction B W = α 2 µ 0 M s N n ≈ 2.6 mT using N n = ∆ πD ln 2 [22], and micromagnetic simulations [21]), at which point V abruptly drops due to the onset of precession of φ. We note that due to weak numerical noise in our implementation, some BLs are present even for σ = 0, and hence the σ = 0 curve shown in Fig.…”
supporting
confidence: 82%
“…The motion of BLs, separating regions of different chiralities of the Bloch DW, mediates largescale precession of the DW magnetization in an analogous manner to dislocation motion mediating plastic flow in crystals. Such effects were recently studied by full micromagnetic simulations of Barkhausen noise [21]. However, micromagnetic simulations describing the magnetization dynamics everywhere in the system are limited to small system sizes, resulting in significant finite size effects.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it was recently shown that scaling exponents describing Barkhausen jumps in thin ferromagnetic films of Pt/Co/Pt obtained by full micromagnetic simulations cannot be distinguished from those expected for the much simpler quenched EW equation. Thus, commonly used simple models based on describing domain walls as elastic lines correctly capture the large-scale critical dynamics of the system [32]. On the other hand, this approach is computationally expensive, thus limiting the system sizes that can be studied in reasonable times.…”
Section: Introductionmentioning
confidence: 99%
“…Analogous behavior has been observed in plastic deformation of sheared materials, where local pinning sites similarly can distort the free energy landscape and allow for seemingly "uphill" motion. [37,38] Numerical simulations of domain-wall motion in disordered perpendicular-anisotropy thin films [39] likewise have observed a small fraction of reversepolarity events. The occurrence probability of these precursor events is strongly temperature dependent, with approximately 5% of the 80 mK events showing a precursor, decreasing to 1% at 250 mK and less than 0.1% at 500 mK and above where thermal fluctuations dominate.…”
mentioning
confidence: 93%